Colored thermal camouflage and anti-counterfeiting with programmable In3SbTe2 platform - Zhou Sihong; Dong Shikui; Guo Yanming; Shuai Yong; Xu He-Xiu; Hu Guangwei (Nanophotonics)
Camouflage is an important technology in various scenarios. Usually, this involves the visible compatibility of the background, which however is facile under infrared thermal radiation detection. The simultaneous visible and thermal camouflage are challenging because it requires full and decoupled manipulations of visible reflection and infrared emissivity using one single device, let alone to its adaptivity to complex environments. Here, we report a programmable, colored thermal camouflage at 3–5 μm and 8–14 μm based on mode coupling in phase-change In3SbTe2 materials. A series of industry-friendly colored multilayer thermal emitters are designed consisting of an anti-reflectance layer for structure coloration above a coupled nanocavity for IR modulation, which easily realizes the complete decoupled control of visible color and infrared emissivity. Our solution features independent structural visible colors in the full visible range and continuously programmable dual-band emissivity modulation with up to 90 % absolute tuning range. Our work facilitates near optimal camouflage and anti-counterfeiting solution for visible-infrared multi-band compatibility of complex environments under different temperatures and colored appearances.